Early Cessation of Adenosine Diphosphate Receptor Inhibitors Among Acute Myocardial Infarction Patients Treated With Percutaneous Coronary Intervention: Insights From the TRANSLATE-ACS Study (Treatment With Adenosine Diphosphate Receptor Inhibitors. (November 2016) - Fosbøl, Emil L.; Ju, Christine; Anstrom, Kevin J.; Zettler, Marjorie E.; Messenger, John C.; Waksman, Ron; Effron, Mark B.; Baker, Brian A.; Cohen, David J.; Peterson, Eric D.; Wang, Tracy Y.
Abstract : Background—: Guidelines recommend the use of adenosine diphosphate receptor inhibitor (ADPri) therapy for 1 year postacute myocardial infarction; yet, early cessation of therapy occurs frequently in clinical practice. Methods and Results—: We examined 11 858 acute myocardial infarction patients treated with percutaneous coronary intervention discharged alive on ADPri therapy from 233 United States TRANSLATE-ACS study (Treatment With Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome) participating hospitals to determine the prevalence of early ADPri cessation (within 1 year), patient-reported reasons for cessation, and associated risk of major adverse cardiovascular events at 1 year. Overall, 2514 (21.2%) of percutaneous coronary intervention–treated patients stopped ADPri by 1 year postmyocardial infarction; the median time from discharge to cessation was 200.5 days (25th, 75th percentiles: 71, 340). Among those with early ADPri cessation, 53.9% received drug-eluting stents and had a median duration of 301 treatment days (25th, 75th percentiles: 137, 353); 33.3% of drug-eluting stent patients stopped treatment within 6 months compared with 64.2% of bare metal stent patients. Those discharged on prasugrel (versus clopidogrel) had a slightly higher likelihood of early ADPri cessation (23.2% versus 21.0%; P =0.03; adjusted hazard ratio, 1.28; 95% confidence interval, 1.17–1.40). Patient-reported reasons for early ADPri cessation included physician-recommended discontinuation (54%), as well as patient self-discontinuation, because of cost (19%), medication side effects (9%), and procedural interruption (10%). Using a time-dependent covariate model, early cessation of ADPri therapy was associated with increased major adverse cardiovascular event (adjusted hazard ratio, 1.40; 95% confidence interval, 1.19–1.65; P <0.0001). Conclusions—: One in 5 percutaneous coronary intervention–treated myocardial infarction patients stopped ADPri treatment within 1 year. Early cessation was associated with increased major adverse cardiovascular event risk. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01088503. Abstract : Supplemental Digital Content is available in the text.